Reparo em áreas de reconstrução onlay, empregando enxertos em bloco associados a diferentes tipos de membranas regenerativas. Estudo histológico em coelhos - Freitas, Caio Peixoto de (2015)
The purpose of this study was to evaluate the bone repair process in onlay reconstruction of areas using two different substrates, for membranes of different times of degradation and nature. To this were used twenty-four adult male rabbits (Oryctolagus cunilicus), which received the calvaria ostectomies region of rabbits through an 8mm trephine. Critics surgically created osseous defects will be filled according to the following groups: Group I: autogenous bone graft and Group II: bovine hydroxyapatite block, which will be subdivided into: Subgroup A: absorbable membrane slow degradation, Subgroup B: absorbable membrane slow degradation in double layer Subgroup C: absorbable membrane of rapid degradation and D Subgroup: control group, without the presence of regenerative membranes. The animals were euthanized in periods of 03 (three) and six (06) months, with 12 animals per period. After euthanasia, the surgical site was reopened for removal of anatomical parts trephine drill aid 10mm internal diameter. These specimens were subjected to histological processing and paraffin embedding to obtain cuts with 6 mm thick, obtained in microtome. The histological sections were stained with hematoxylin and eosin (HE) for histological analysis